(3EbJUGO GdeYQaI (B:s (3GdCSS GdfXQjI hGdJWHjb aj GdeUGQa GdJLGQjI (B/s - (3GdNRQLj, KQjG YHO GdQMjes; (3GdHGQhOj, TQjf HOQj s ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2012)
(3GdeYQaI, eaGgje fXQjI hadSajI(B- (3GdCWQ GdacQjI hGdadSajI dEbJUGO GdeYQaI(B- (3GdefXheGJ GdeMaRI ddESJKeGQ aj EbJUGO GdeYQaI(B- (3GdHYO GdeYQaj aj NOeGJ GdeUGQa GdJLGQjI(B- (3efXheI GdeUGQa GdEdcJQhfjI(B-(3GSJQGJjLjI Yed GdeUGQa GdEdcJQhfjI(B- (3BdjI JShjI GdeOahYGJ GdEdcJQhfjI aj Xd EbJUGO GdeYQaI(B- (3efXheI hSGFd GdOaY GdEdcJQhfjI(B- (3fXe GdOaY hGdJMhjd GdEdcJQhfjs
Keywords: (3GdEbJUGOs; (3GdHfhc GdJLGQjIs; (3GdeYQaIs